2001
DOI: 10.1002/1521-3765(20010702)7:13<2758::aid-chem2758>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid-Crystalline Silsesquioxane Dendrimer Exhibiting Chiral Nematic and Columnar Mesophases

Abstract: A hexadecamer, first-generation, octasilsesquioxane liquid-crystalline dendrimer was synthesized by a platinum-catalyzed hydrosilylation reaction of the parent first-generation vinyl octasilsesquioxane dendrimer with a modified, laterally substituted mesogen. The structure and purity of the octasilsesquioxane substrate was confirmed by 1H, 13C, and 29 Si NMR spectroscopy, microanalysis, and size exclusion chromatography (SEC). The mesogenic substrate was found to exhibit only a chiral nematic phase, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 9 publications
1
68
0
4
Order By: Relevance
“…42,117 The dendritic design is effective to induce liquid crystallinity for complex molecules. [120][121][122][123][124] Silsesquioxanes have been used as scaffolds of supermolecular liquid crystals because organic substituents can be easily tethered to the vertices of the polyhedra. 120,121 Mehl and Goodby 122 reported octasilsesquioxane dendrimers exhibiting LC phases by introducing cyanobiphenyl mesogens on the periphery.…”
Section: Dendritic Design For Lc Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…42,117 The dendritic design is effective to induce liquid crystallinity for complex molecules. [120][121][122][123][124] Silsesquioxanes have been used as scaffolds of supermolecular liquid crystals because organic substituents can be easily tethered to the vertices of the polyhedra. 120,121 Mehl and Goodby 122 reported octasilsesquioxane dendrimers exhibiting LC phases by introducing cyanobiphenyl mesogens on the periphery.…”
Section: Dendritic Design For Lc Polymersmentioning
confidence: 99%
“…The mesomorphic properties can be tuned by number, density and orientation of the attachment of rigid-rod moieties bound to the central cores. 123 In general, laterally attached mesogens induce nematic phases, whereas terminally attached mesogens afford smectic phases. 120,121 By combining these two different types of mesogens, 'Janus' liquid crystal 24 has been developed.…”
Section: Dendritic Design For Lc Polymersmentioning
confidence: 99%
“…A very detailed study of modifications of cubic silsesquioxanes with various mesogens and subsequent coupling via Pt or Pd catalyst opens an alternative route to new LC materials reported by Laine et al [17,18]. Richardson et al [19] reported a hexadecamer, first-generation, octasilsesquioxane liquid crystalline dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…For many applications, such as displays, optical data storage materials, switches and shutters, etc., linear, high molecular weight materials exhibit a too long response time, when supramolecular orientation is achieved by changes in external electric or magnetic fields. [2] Therefore, much current research concentrates on so called hybrid liquid crystals of intermediate molecular weight, especially oligomers such as cyclic [3,4], linear [5,6] siloxanes, and structures of globular shape, having topologies giving decreased viscosity in melt, while preserving the robust mechanical properties of polymers (silsesquioxanes, dendritic and dendrimeric systems [7,8]). …”
Section: Introductionmentioning
confidence: 99%